Comparison of Carrier and de novo Pathogenic Variants in a Chinese DMD/BMD Cohort - Lin, Jinfu; Li, Huan; Liao, Ziyu; Wang, Liang; Zhang, Cheng (Frontiers in Neurology, 2021)
Background: Duchenne and Becker muscular dystrophy (DMD/BMD) are X-linked recessively inherited neuromuscular disorders caused by deletions, duplications, or small mutations in the DMD gene. With advances in prenatal diagnosis decreasing the number of affected offspring from carrier mothers, the frequency of de novo variants could increase. Therefore, determining the differences between carrier and de novo variants of the DMD gene, which are rarely explored, is important for trial planning and genetic diagnosis in the future. Methods: A total of 440 patients, 349 of which have DMD and 91 have BMD, who were diagnosed in our department between 2012 and 2019, along with their respective mothers, were included in this study. Multiplex ligation-dependent probe amplification was used to detected deletions and duplications in patients and their mothers. Small mutations were detected using next generation sequencing in the patients, followed by using Sanger sequencing in the mothers. Results: Deletions, duplications, and small mutations were identified in 204, 46, and 99 of the 349 patients with DMD, and in 50, 10, and 31 of the 91 patients with BMD, respectively. De novo deletions were more concentrated in hotspot regions than in carrier deletions of DMD/BMD. No clear bias was observed in the variant distribution between carriers, de novo duplications, and small mutations in DMD/BMD. The carrier frequency of DMD (61.6%) was lower than that of BMD (69.2%), but the difference was not statistically significant. The carrier frequency of deletions of the DMD gene (51.2%) was significantly lower than that of duplications (75%) and small mutations (81.5%). Conclusion: Compared to de novo deletions, deletions from carrier mothers had a wider distribution. Moreover, there was no significant difference between the carrier frequencies of DMD and BMD. Duplications and small mutations were more commonly inherited, while deletions were present de novo.